Reducing Mask-Related Pressure Injuries in Pediatric Patients During Noninvasive Ventilation by Targeting Patient Mask Leak: A Quality Improvement Initiative. Issue 6 (November 2022) - Lauderbaugh, Denise L.; Popien, Toni L.; Lesser, Daniel J.; Bhattacharjee, Rakesh; Pfrommer Puleo, Cheryl
Abstract : PURPOSE: To compare outcomes following implementation of patient mask leak range of 25 to 55 liters per minute (lpm) to guide strap tension of sleep masks during noninvasive ventilation against baseline data with no patient mask leak range on number of noninvasive mask-related pressure injuries (PIs). PARTICIPANTS AND SETTING: All noninvasively ventilated pediatric acute care patients admitted to general wards and intensive care units between February 1, 2018, and February 1, 2019, in a quaternary hospital in the southwest United States. APPROACH: Using the Plan Do Study Act model, we employed an intervention to examine the rate of PIs per noninvasive positive pressure ventilation (NIPPV) days and patient-days before and after implementation of patient mask leak parameters between 25 and 55 lpm to guide mask strap tension. Since patients are at an increased risk of sleep mask-related PIs only when on NIPPV, we sought to describe that as number or PIs per number of days at risk, described as NIPPV days, and patient days which is the traditional denominator for wounds and hospital-acquired conditions. OUTCOMES: Preintervention, 6 out of 115 subjects (5.2 %) incurred PI at a rate of 0.51 per 100 NIPPV days or 0.26 per 1000 patient-days. Of the 1932 NIPPV days since education was completed, only 1 subject out of 87 (1.1%) incurred a high-stage PI (0.05/100 NIPPV days—a 96.79% reduction or 0.05/1000 patient-days—a 92.86% reduction). Upon reaching more than 90% compliance with patient mask leak range in December 2018, 1221 NIPPV days resulted in 0 noninvasive mask-related PIs. Greater than 90% compliance with a patient mask leak of 25 to 55 lpm allowed us to successfully achieve our hospital's operating plan goal of 0.15 of 1000 patient-days within this group. IMPLICATIONS FOR PRACTICE: Maintaining a patient mask leak range between 25 and 55 lpm should be considered as part of proper fit for pediatric patients using NIPPV with a mask. Additional work is needed to assess this leak range in more children and in studies conducted at multiple sites. Video Abstract: Video 1 Reducing mask-related pressure injuries in pediatric patients during ventilation by targeting patient mask leak: A quality improvement initiative.